Properdin: A Novel Target for Neuroprotection in Neonatal Hypoxic-Ischemic Brain Injury - Sisa, Claudia; Agha-Shah, Qudsiyah; Sanghera, Balpreet; Carno, Ariela; Stover, Cordula; Hristova, Mariya (Frontiers in Immunology, 2019)
Background: Hypoxic-ischemic (HI) encephalopathy is a major cause of neonatal mortality and morbidity, with a global incidence of 3 per 1,000 live births. Intrauterine or perinatal complications, including maternal infection, constitute a major risk for the development of neonatal HI brain damage. During HI, inflammatory response and oxidative stress occur, causing subsequent cell death. The presence of an infection sensitizes the neonatal brain, making it more vulnerable to the HI damage. Currently, therapeutic hypothermia is the only clinically approved treatment available for HI encephalopathy, however it is only partially effective in HI alone and its application in infection-sensitized HI is debatable. Therefore, there is an unmet clinical need for the development of novel therapeutic interventions for the treatment of HI. Such an alternative is targeting the complement system. Properdin, which is involved in stabilization of the alternative pathway convertases, is the only known positive regulator of alternative complement activation. Absence of the classical pathway in the neonatal HI brain is neuroprotective. However, there is a paucity of data on the participation of the alternative pathway and in particular the role of properdin in HI brain damage. Objectives: Our study aimed to validate the effect of global properdin deletion in two mouse models: HI alone and LPS-sensitized HI, thus addressing two different clinical scenarios. Results: Our results indicate that global properdin deletion in a Rice-Vannucci model of neonatal HI and LPS-sensitized HI brain damage, in the short term, clearly reduced forebrain cell death and microglial activation, as well as tissue loss. In HI alone, deletion of properdin reduced TUNEL+ cell death and microglial post-HI response at 48 h post insult. Under the conditions of LPS-sensitized HI, properdin deletion diminished TUNEL+ cell death, tissue loss and microglial activation at 48 h post-HI. Conclusion: Overall, our data suggests a critical role for properdin, and possibly also a contribution in neonatal HI alone and in infection-sensitized HI brain damage. Thus, properdin can be considered a novel target for treatment of neonatal HI brain damage.